Comportamento mecânico de misturas asfálticas a quente dosadas pelas metodologias marshall e superpave com diferentes granulometrias - Vasconcelos, Kamilla Lima (2004)
The use of new asphalt mixtures and a new design process are still in consolidation at the universities and departments of transportation in Brazil. The main objective of this research is to design hot mix asphalts with different aggregate gradations using both the Marshall and Superpave (level 1) design method. The differences between these two design methodsare: (i) theoretical maximum specific gravity (Gmm) determination; (ii) compaction method; and (iii) short-term aging of the mixtures. It was selected to this research dense mixtures with 4%air voids, but with continuous and gap-graded gradations. The Gmm was determined indirectly from the mixture composition and the relative densities of the constituents of the mixes, and through the uses of a vacuum pump (Rice method). Short-term aging was considered just in the Superpave design, with 2 hours inthe oven at the compaction temperature. The design results showed higher optimum asphalt content for the Superpave mixtures. The mechanical behavior of the mixtures was evaluated by: the indirect tensile strenght, resilient modulus, fatigue life (stress controlled), resistance to moisture damage, and permanent deformation.